Adaptive observer-based tracking controller designs for a distributed energy storage device. Issue 13 (2018) - Romero, J.G.; Cisneros, R.; Khan, M.T.; Méndez-Barrios, C.F.
Abstract: This paper considers three different tracking control schemes for a distributed energy storage system. The system is made up of a battery and a synchronous boost converter which, connected to a dc bus, allows bidirectional power flow, enabling the battery for charging and discharging operation modes. First, we derive the controllers assuming all parameters and variables to be known. Then, designing an adaptive observer, the three approaches are extended for the case in which the current is not measured and the internal converter resistances are unknown. Stability of the resulting closed-loop system is proved for both cases. The approaches are compared, tested and validated in a setting consisting of a dc grid with renewable sources connected to it.